Dengue Haemorrhagic Fever Control Competencies among Public Health Volunteers (PHV) in Rayong Province, Thailand - Suengthaworn, Thongchai (Journal of Health Science of Thailand, 2018)
The study was aimed at identifing and comparing the competency level of disease control and prevention competencies among Public Health Volunteers-PHV in Rayong Municipality of Rayong province on the Eastern Seaboard of Thailand. A simple random sampling yielded 201 PHVs who participated in the study. Data collection tool was a survey questionnaire developed specifically for this study, with content validity of items-CVI-at 0.85, and Cronbachีs alpha at 0.98. Data analysis used descriptive statistical methods, t-test and F-test, p ≤ 0.05 Results showed that the majority of the study volunteers (43.8%) had the competency at a medium level ( 65.38, SD 16.13). Item-wise, they showed competency with regards to the ability to demonstrate the use of abate sand in lavae control at a medium level ( 19.99, SD4.8), while the lowest level ( 8.62, SD 2.6) of competency among the volunteers was development of public participation. The study volunteers also exhibited the highest ability in the activities related to vector control ( 75.82, SD 18.94), and the lowest ability in engaging the community in Dengue haemorrhagic fever control by paracetamol ( 56.50, SD 28.04). It was also found that male volunteers, and volunteers who just started to work demonstrated significantly higher ability to perform work. It is recommended that capacity building for PHVs is needed and includes proper recruitment, human resource development, and orientation to close the gaps in public participation and primary medical care.